2012
DOI: 10.3389/fpsyg.2012.00385
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Evidence Linguistic Processes Precede Perceptual Simulation in Conceptual Processing

Abstract: There is increasing evidence from response time experiments that language statistics and perceptual simulations both play a role in conceptual processing. In an EEG experiment we compared neural activity in cortical regions commonly associated with linguistic processing and visual perceptual processing to determine to what extent symbolic and embodied accounts of cognition applied. Participants were asked to determine the semantic relationship of word pairs (e.g., sky – ground) or to determine their iconic rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
42
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 52 publications
6
42
1
Order By: Relevance
“…Nonetheless, supporting evidence has been found in a range of paradigms, including behavioral Louwerse & Connell, 2011;Santos et al, 2011), electrophysiological (Louwerse & Hutchinson, 2012), and neuroimaging studies. For instance, when asked to list properties for a given concept, Santos et al (2011) found that people tended to begin by listing linguistic associates of the word (e.g., bee → hive, honey, sting) and later moved onto non-associates that were consistent with simulating the concept in a broad situational context (bee → wings, summer, flowers).…”
Section: What Advantage Has Linguistic Information?mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, supporting evidence has been found in a range of paradigms, including behavioral Louwerse & Connell, 2011;Santos et al, 2011), electrophysiological (Louwerse & Hutchinson, 2012), and neuroimaging studies. For instance, when asked to list properties for a given concept, Santos et al (2011) found that people tended to begin by listing linguistic associates of the word (e.g., bee → hive, honey, sting) and later moved onto non-associates that were consistent with simulating the concept in a broad situational context (bee → wings, summer, flowers).…”
Section: What Advantage Has Linguistic Information?mentioning
confidence: 99%
“…Empirical evidence for its utility in conceptual processing has come from a range of tasks, including property verification (Louwerse & Connell, 2011), property generation (Santos, Chaigneau, Simmons, & Barsalou, 2011;Simmons, Hamann, Harenski, Hu, & Barsalou, 2008), conceptual combination , semantic relatedness and spatial iconicity (Louwerse & Hutchinson, 2012;Louwerse & Jeuniaux, 2010), metaphor comprehension Liu, Connell & Lynott, 2018), and SNARC effects (Hutchinson & Louwerse, 2014). For example, the order of word distribution in English is highly directional (e.g., "root" tends to be mentioned before "branch" more often than vice versa).…”
mentioning
confidence: 99%
“…In other words, people have a linguistic shortcut available during conceptual processing, in that computationally cheaper information from the linguistic system can usefully inform a response in a particular task before relatively more expensive (but precise) representations are fully available. Support for this idea has come from Louwerse and Connell (2011;see also Jones & Golonka, 2012;Louwerse & Hutchinson, 2012;Solomon & Barsalou, 2004), who examined the ability of the linguistic shortcut to predict modality-switching costs in a property verification task. Switching costs refer to the finding that people are slower to confirm that a perceptual object property is true (e.g., the auditory property leaves can be rustling) when it follows a property from a different modality (e.g., the visual property dew can be glistening), and this processing cost is assumed to arise from the reallocation of attention between modalityspecific areas during representation of the object property in question (Pecher, Zeelenberg, & Barsalou, 2003).…”
mentioning
confidence: 99%
“…Hald et al (2013) find evidence for modality-specific grounded representations when processing negated sentences, and demonstrate differential modulation of the N400 according to whether or not a true vs. false sentence involves modality switching. Louwerse and Hutchinson (2012) show that different tasks rely on linguistic vs. perceptual information to different extents, with activation in linguistic cortical regions preceding activation in perceptual cortical regions when both types of processing were associated with the task.As well as perceptual information, motor information relating to action concepts was also a central topic. In a review of behavioral and neuroimaging work on semantics across different domains (e.g., concrete/abstract words, numbers, and arithmetic), Hauk and Tschentscher (2013) argue that the specific function of sensorimotor areas in processing meaning remains unclear, and suggest that only by employing a combination of methods can causal underpinnings be deduced.…”
mentioning
confidence: 99%
“…Hald et al (2013) find evidence for modality-specific grounded representations when processing negated sentences, and demonstrate differential modulation of the N400 according to whether or not a true vs. false sentence involves modality switching. Louwerse and Hutchinson (2012) show that different tasks rely on linguistic vs. perceptual information to different extents, with activation in linguistic cortical regions preceding activation in perceptual cortical regions when both types of processing were associated with the task.…”
mentioning
confidence: 99%